2003
DOI: 10.1002/jcp.10417
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous activation of several second messengers in hypoxia‐induced hyperpermeability of brain derived endothelial cells

Abstract: In vivo, ischemia is known to damage the blood-brain barrier (BBB) leading to the development of vasogenic brain edema. Hypoxia-induced vascular endothelial growth factor (VEGF) has been shown to be a key regulator of these permeability changes. However, the signaling pathways that underlie VEGF-induced hyperpermeability are incompletely understood. In this study, we demonstrate that hypoxia- and VEGF-induced permeability changes depend on activation of phospholipase Cgamma (PLCgamma), phosphatidylinositol 3-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 68 publications
(85 reference statements)
7
60
0
Order By: Relevance
“…This idea is supported by a study (20) that showed that PKC mediates BBB function by altering ICAM and fluid phase endocytosis in tumor necrosis factor ␣-treated endothelial cells. It is also supported by a study (24) that demonstrated a minimal role for PKC in H-induced BBB permeability and TJ alterations induced by H and VEGF.…”
Section: Discussionmentioning
confidence: 56%
“…This idea is supported by a study (20) that showed that PKC mediates BBB function by altering ICAM and fluid phase endocytosis in tumor necrosis factor ␣-treated endothelial cells. It is also supported by a study (24) that demonstrated a minimal role for PKC in H-induced BBB permeability and TJ alterations induced by H and VEGF.…”
Section: Discussionmentioning
confidence: 56%
“…Fischer et al believed that the hyperpermeability induced by H 2 O 2 was caused by activation of p44/42 mitogen activated protein (MAP) kinase through changing the localization of tight junction proteins. 18) In another study of colonic epithelium, it was found that protein kinase C, not MAPK, is involved in the regulation of ZO-1. Meanwhile, Sheth et al found that the PI3K signaling pathway is involved in oxidative stress-induced disruption of tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicated that VASP levels increased in the membrane and cytoskeletal fractions after 1 h of hypoxia, supporting the idea that there is an early dynamic change in the actin cytoskeleton. This mobilization is likely to be mediated through multiple pathways, including PKG (15,63), MLCK (34), and RhoA/ ROCK (27).…”
Section: Discussionmentioning
confidence: 99%